FUNÇÕES E ANÁLISE BIOMÉTRICA DA AVEIA BRANCA FRENTE ÀS FORMAS DE FORNECIMENTO DE NITROGÊNIO - Mantai, Rúbia D.; Costa, Juliane S. P.; Sausen, Airam T. Z. R.; Gewehr, Ewerton; Romitti, Marcos V.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo